2018
DOI: 10.1021/acsomega.8b01743
|View full text |Cite
|
Sign up to set email alerts
|

Facile Conversion of Toxic Cigarette Butts to N,S-Codoped Carbon Dots and Their Application in Fluorescent Film, Security Ink, Bioimaging, Sensing and Logic Gate Operation

Abstract: The present work is emphasized on converting toxic cigarette butts (CBs) into highly fluorescent N,S-codoped carbon dots by a facile hydrothermal approach and exploring their multiple applications. The as-produced carbon dots (CBCDs) exhibited bright and stable fluorescence with a quantum yield of 26% and used as a label-free probe for “on–off–on” sequential detection of Fe3+ and ascorbic acid (AA). The fluorescence of CBCDs can be significantly quenched by Fe3+ ions through static quenching and restored upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(64 citation statements)
references
References 68 publications
0
59
0
Order By: Relevance
“…Considering the proportion of incorporated Ag + ions in the bimetallic NCs, YES and NOT logic gates could be built. As per previous reports, construction of various logic gates solely depends on external factors such as association and dissociation of sensing ions with or from a fluorophore and by alterations of pH and temperature of the environment [68][69][70][71][72]. On the contrary, here we have attempted to construct logic gates without influence of any such external factor.…”
Section: Resultsmentioning
confidence: 80%
“…Considering the proportion of incorporated Ag + ions in the bimetallic NCs, YES and NOT logic gates could be built. As per previous reports, construction of various logic gates solely depends on external factors such as association and dissociation of sensing ions with or from a fluorophore and by alterations of pH and temperature of the environment [68][69][70][71][72]. On the contrary, here we have attempted to construct logic gates without influence of any such external factor.…”
Section: Resultsmentioning
confidence: 80%
“…Doped/co-doped CQDs do possess special abilities to optically sense (based on color change/quenching process) different targets including metal ions (mainly Fe 3+ and Hg 2+ ions), Similar to the above study, Bandi et al have also explored the potentiality of N and S co-doped CQDs for fluorescent ink for use in anti-counterfeiting [164]. For this purpose, the following steps are followed: a sketch pen is initially filled with N and S co-doped CQDs based aqueous solution and is used for writing some text (for instance "Osmania University") on commercial filter paper, and then the filter paper is viewed under visible and UV light.…”
Section: Optical Sensorsmentioning
confidence: 79%
“…When the system is subjected to the two inputs together, the strong interaction between metal ions and chelators releases metal ions from the surface of N and S co-doped CQDs and the output signal is "1 '. In another similar study, Bandi et al converted toxic cigarette butts into N and S co-doped CQDs (with QY of 26%) in the presence of sulphuric acid via hydrothermal approach, for further construction of an IMPLICATION logic gate [164]. Herein, cigarette butts were chosen as precursors, since they are mainly composed of cellulose acetate fibers, and also contain minor amounts of chemicals including polycyclic aromatic hydrocarbons, nicotine, aromatic amines, N-nitrosamine, and tarlike components that are trapped during smoking.…”
Section: Molecular Logic Gatesmentioning
confidence: 99%
“…The treatments consisted of pristine, polyacrylic acid (PAA), and polyethylenimine (PEI) surface modified CQDs. The authors reported that the CQDs-PEI significantly decreased total fresh weight and altered stress enzymes [2]. However, the exposure period does not permit the prediction of these effects in a life-cycle plant growth.…”
Section: Discussionmentioning
confidence: 99%
“…Of late, CQDs have been synthesized from cigarette waste [1,2,9] and have also been sourced from diesel exhaust [25]. Yet, studies concerning the environmental risks of CQDs to both plant and aquatic lifeforms appear to be largely inadequate and have been ignored.…”
Section: Cqd Chemical Footprint and The Biomementioning
confidence: 99%